Thrombopoietin Receptor Agonists in Treatment of Idiopathic Thrompocytopenic Purpura (Primary Immune Thrombocytopenia): Efficacy and Safety in Everyday Clinical Practice - II Zotova; SV Gritsaev; ER Shilova; NA Potikhonova; KМ Abdulkadyrov; AV Chechetkin (Клиническая онкогематология)
Background & Aims. The use of thrombopoietin receptor agonists (aTPO-r) is a new approach to the treatment of patients with idiopathic thrompocytopenic purpura (ITP) irresponsive to other methods. Data on the efficacy and safety of aTPO-r outside the frames of clinical trials are limited. The aim of the study is to evaluate the efficacy of the therapy in the routine clinical practice as the second and subsequent lines of therapy, as well as the frequency and nature of complications of the treatment in chronic ITP patients. Methods. Data on 58 adult patients (median age: 56 years) with chronic ITP were retrospectively evaluated; 43 (74 %) of them were treated with romiplostim and 15 (26 %) patients received eltrombopag. Two or more lines of prior therapy were ineffective in 19 (33 %) patients (14 from the romiplostim group and 5 from the eltrombopag group). aTPO-r was prescribed and adjusted according to the prescription guidelines. The efficacy of the treatment was assessed based on the platelet response and the possibility of achieving a sustained response after discontinuation of the therapy. Hemorrhagic manifestations were classified according to the WHO bleeding scale. The safety assessment is conducted by identifying adverse events (AEs) and lab test abnormalities. Treatment-related adverse events was assessed according to the Common Terminology Criteria for Adverse Events (CTCAE) v3.0.